Synthesis and Characterization of NickelâMagnesium Catalyst Supported on Reduced Graphene Oxide - Mohd Ridzuan, N.D. (Springer Science and Business Media B.V., 2021)
In this study, nickelâmagnesium catalyst supported on reduced graphene oxide nanosheets was synthesized. rGO support was characterized by X-ray diffraction (XRD), surface area and porosity, and thermogravimetric analysis, and fourier-transform infrared (FTIR) and Raman spectroscopy to understand its physicochemical properties. The results revealed that the edge-oxidized rGO has high surface area (258.11Â m2gâ1) with approximately 36 multi graphitic layers where interlayer spacing is 0.336Â nm each. High thermal stability of rGO makes it an excellent support to be used for high-temperature catalytic activity. Subsequently, rGO supported catalysts were synthesized via incipient wetness impregnation method. The amount of Ni was fixed at 20Â wt whilst Mg was varied atÂ 0 wtÂ and 5Â wt relative to rGO content to assess its effect as second metal towards properties of the catalyst. X-ray diffractograms of Ni20/rGO and Ni20Mg5/rGO demonstrated formation of new peaks due to presence of NiO and NiOâMgO whereas (002) rGO peak at 26.5Â° does not show obvious changes, concluding the stability of rGO after the impregnation and calcination processes. Upon impregnation, the surface area and porosity of Ni20/rGO is lower than that of rGO due to dispersion of Ni metal on the rGO surface. BET surface area of Ni20Mg5/rGO catalyst further decreases to 103.95Â m2gâ1 due to the addition of metal content but its porosity is higher than Ni20/rGO. Hence, it is postulated that Ni and Mg metal form solid solution (NiOâMgO) on rGO nanosheets which has bigger particle size compared to NiO, lowering its penetration into rGO mesopores. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.